PENCEMARAN NAMA BAIK DALAM PEMBERITAAN PERS - Hadibah Zachra Wadjo (Faculty of Law, Universitas Pattimura, 2011)
Development of the press or mass media today are influenced by several factors indicate changes in the face of the press or mass media ie, before delivering the news the press does not investigate the validity or subjects who reported whether true or not, obtained Press Publishing Business License (SIUUP) and improving the quality of journalism inadequate. Then the rise of new media including the Internet, multimedia technology, and next faces the press institutionalism practice that is due to pressure owners of capital, government pressure and pressure groups both internally and externally. Results showed, after the press tripped law have been regarded as preaching defame a person or group then the solution is still wearing articles of the Penal Code. It is not in line with what is desired by members of the press or mass media, because there are no rules that specifically regulates defamation committed by the press or mass media as well as Law No. 40 of 1999 on the Press, did not set any single article regarding defamation, only regulate the right of reply, rejected the right and the right correction.